"Network" socio-hydrology: a case study of causal factors that shape the Jaguaribe River Basin, Ceará-Brazil. Issue 6 (26th April 2021) - Frota, Renata Locarno; Souza Filho, Francisco de Assis; Barros, Luis Silva; Silva, Samíria Maria Oliveira; Porto, Victor Costa; Rocha, Renan Vieira
ABSTRACT: Socio-hydrology has recently garnered attention as a promising research paradigm among hydrologists. In this paper, we argue that viewing the socio-hydrological systems as a network of causal factors can assist in these efforts by revealing emergent properties of socio-hydrological systems. These factors, which are neither actors nor affiliations but symbolic representations of miscellaneous phenomena, represent the key variables affecting socio-hydrological system behaviour. Despite being crucial for understanding system dynamics, these factors are not captured by most equations of coupled human–water coevolutionary models. To demonstrate our method, we use qualitative case study research to analyse the Jaguaribe Basin in Ceará State-Brazil as a network of factors, i.e. mental conceptions, and representations of water resource management experts. We show that most results are unsurprising, exhibiting expected causal relationships. However, there was at least one unexpected result, which showed that the variable "conflict" was the single most sensitive variable to systemic evolution.